Reform of China's Rural Credit Unions : Policy Note - World Bank (Washington, DC, 2013)
The reform of the Rural Credit Unions (RCUs) currently faces a number of major inter-related challenges. These must be resolved if China is to create a 'modern rural financial system'. The key issues facing policy-makers are: Consolidating independent shareholder ownership in order to realize effective corporate governance and create sustainable commercial financial institutions; reshaping the relationship between provincial governments and the RCU system in order to bring to an end direct government administrative intervention in RCU management; preventing government subsidies and special policies, which are intended to ensure that RCUs meet policy goals to support the rural economy, from generating rent-seeking behavior and moral hazards that undermine commercial sustainability; and enabling the growth of a diverse range of rural financial institutions that would create competition and force greater efficiencies in rural financial markets. Policy reforms since 2003 have sought to address these issues, but they have yet to achieve their goal. The need for more change is widely recognized, and the authorities now have the opportunity to implement further reforms in order to create a flexible, diverse, efficient and responsive rural financial market that is both vibrant and disciplined.